2016
DOI: 10.1038/gt.2016.66
|View full text |Cite|
|
Sign up to set email alerts
|

Development of an optimized AAV2/5 gene therapy vector for Leber congenital amaurosis owing to defects in RPE65

Abstract: Leber congenital amaurosis is a group of inherited retinal dystrophies that cause severe sight impairment in childhood; RPE65-deficiency causes impaired rod photoreceptor function from birth and progressive impairment of cone photoreceptor function associated with retinal degeneration. In animal models of RPE65 deficiency, subretinal injection of recombinant adeno-associated virus (AAV) 2/2 vectors carrying RPE65 cDNA improves rod photoreceptor function, and intervention at an early stage of disease provides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 20 publications
(27 reference statements)
1
44
0
1
Order By: Relevance
“…The results of a phase 1/2 trial of gene therapy for LCA showed improved retinal sensitivity; however, cases of inflammation and/or immune responses were reported,17, 18 highlighting the issue of AAV immunogenicity. Improving vector efficiency through inclusion of a posttranscriptional regulatory element (PRE) within the transgene cassette may help overcome this problem by allowing a lower dose of AAV to be delivered to achieve any given treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a phase 1/2 trial of gene therapy for LCA showed improved retinal sensitivity; however, cases of inflammation and/or immune responses were reported,17, 18 highlighting the issue of AAV immunogenicity. Improving vector efficiency through inclusion of a posttranscriptional regulatory element (PRE) within the transgene cassette may help overcome this problem by allowing a lower dose of AAV to be delivered to achieve any given treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…In an LCA animal model, subretinal injection of recombinant AAV 2/5-OPTIRPE65 improved retinal function against retinal degeneration in Rpe65 knockout mice [48] , and long-term transduction of RPE cells and photoreceptors in rats and nonhuman primates was observed [49] . AAV2 delivery of the RPE65 gene subretinally to the retina showed restoration of vision, rescuing the numbers of remaining photoreceptors both in young and old RPE65-mutant/deficient dogs [50,51] .…”
Section: Gene Therapymentioning
confidence: 98%
“…Clinical trials using gene therapy to treat other debilitating genetic conditions such as spinal muscular atrophy, 57 which has also recently been granted FDA approval, and junctional epidermolysis bullosa 58 are also showing considerable promise with good safety profiles and functional improvement. Although evaluation is ongoing and the longer-term impact remains uncertain, with other trials for LCA (NCT00643747) reporting a decline in the degree of visual improvement 59 and the subsequent development of an optimised AAV5 viral vector and transgene expression cassette to improve retinal transduction and yield higher levels of RPE65, 60 these advances all lend strong support to the use of directly administered gene therapies forming a core part of a clinician's toolkit when treating intractable illnesses in the foreseeable future.…”
Section: Gene Therapymentioning
confidence: 99%